Haplothrips second instar larvae (Thysanoptera: Phlaeothripidae); character states and key to Central European species - Kucharczyk, Halina; Stanisławek, Kinga (Zootaxa, 2020)
Descriptions and images of character states are provided of the second instar larvae of 16 species of Haplothrips. Specimens used are from Poland and surrounding countries, and an identification key is presented. The most important qualitative features concern colour, sclerotization and cuticular sculpture of some body parts, spiracle structure, setal lengths and type of setal apices.